Salinity in the coastal CHAR areas : mechanism of desalinisation and resalinisation, approaches for improvement - De Goffau, A. (Mission report (Char Development and Settlement Project II (Bangladesh)), 2002)
Sponsored by various intergovernmental bodies and NGOs.